Accurate identification and documentation of First Nations women and babies attending maternity services: How can we 'close the gap' if we can't get this right?. (18th December 2022) - McLardie‐Hore, Fiona E.; McLachlan, Helen L.; Newton, Michelle S.; Bundle, Gina; Druce, Tanya; Jackomos, Marika; Forster, Della A.
Abstract : Background: Policies and strategies addressing the health inequities experienced by First Nations peoples are critical to ensuring the gap in outcomes between First Nations and non‐Indigenous peoples is closed. The identification of First Nations peoples is vital to enable the delivery of culturally safe and sensitive health care. Complete and accurate health data are essential for funding and evaluation of such initiatives. Aims: To describe the processes used and accuracy of identification and documentation of First Nations mothers and babies during the period of the implementation of a culturally responsive caseload model of maternity care at three major metropolitan maternity services in Melbourne, Australia. Materials and methods: A cross‐sectional study was conducted using administrative and clinical data. Results: There was variation in when and how First Nations identification was asked and documented for mothers and babies. Errors included 14% of First Nations mothers not identified at the first booking appointment, 5% not identified until after the birth and 11% of First Nations babies not identified in the Victorian Perinatal Data Collection documentation. Changes to documentation and staff education were implemented to improve identification and reduce inaccuracies. Conclusions: To improve disparities in health outcomes, mainstream health services must respond to the needs of First Nations peoples, but improved care first requires accurate identification and documentation of First Nations peoples. Implementing and maintaining accuracy in collection and documentation of First Nations status is essential for health services to provide timely and appropriate care to First Nations people and to support and grow culturally appropriate and safe services.